2014
DOI: 10.1016/j.ymgme.2013.12.258
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening and diagnosis of mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPS) are caused by deficiency of lysosomal enzyme activities needed to degrade glycosaminoglycans (GAGs), which are long unbranched polysaccharides consisting of repeating disaccharides. GAGs include: chondroitin sulfate (CS), dermatan sulfate (DS), heparan sulfate (HS), keratan sulfate (KS), and hyaluronan. Their catabolism may be blocked singly or in combination depending on the specific enzyme deficiency. There are 11 known enzyme deficiencies, resulting in seven distinct forms of MPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 92 publications
(130 reference statements)
2
26
0
2
Order By: Relevance
“…Total KS level in the plasma/serum can be used as a biomarker for MPS IVA (Tomatsu et al , 2010c(Tomatsu et al , 2012b(Tomatsu et al , 2013aHintze et al 2011;Martell et al 2011); however, there are substantial overlaps of KS values between control subjects and MPS IVA patients, especially for patients older than 15 years of age, and consequently total KS alone is not a good biomarker for MPS IVA patients of all ages. GALNS, an enzyme involved in the first step of degradation of polymer KS, hydrolyzes the C (6) sulfate of Gal from di-sulfated KS, Gal(6S)b1 !…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Total KS level in the plasma/serum can be used as a biomarker for MPS IVA (Tomatsu et al , 2010c(Tomatsu et al , 2012b(Tomatsu et al , 2013aHintze et al 2011;Martell et al 2011); however, there are substantial overlaps of KS values between control subjects and MPS IVA patients, especially for patients older than 15 years of age, and consequently total KS alone is not a good biomarker for MPS IVA patients of all ages. GALNS, an enzyme involved in the first step of degradation of polymer KS, hydrolyzes the C (6) sulfate of Gal from di-sulfated KS, Gal(6S)b1 !…”
Section: Discussionmentioning
confidence: 99%
“…4GlcNAc (6S). Gel permeation chromatography (GPC)-HPLC study showed that 60 % of KS-I was digested with keratanase II (Tomatsu et al 2013a. Di-sulfated KS (L4; 20 mg/ml), polymer KS (20 mg/ml), and chondrosine for internal standard (IS) (1 mg/ml) supplied by Seikagaku Co. were prepared separately in ddH 2 O.…”
Section: Enzymes and Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…Nas MPSs, o depósito intracelular das GAGs ocorre na maioria das células, ocasionando disfunções celulares e teciduais nos diferentes órgãos (Muenzer 2004). O catabolismo das GAGs pode ser bloqueado isoladamente ou em combinações, podendo ocorrer o acumulo das seguintes GAGs: dermatan sulfato (DS), heparan sulfato (HS), queratan sulfato (QS), e o acido hialurônico (Tomatsu et al 2013). …”
Section: As Mucopolissacaridosesunclassified